Characteristics and outcomes of unsuccessful percutaneous coronary intervention. Issue 3 (31st July 2021) - Biswas, Sinjini; Dinh, Diem; Duffy, Stephen J.; Brennan, Angela; Liew, Danny; Chan, William; Cox, Nicholas; Reid, Christopher M.; Lefkovits, Jeffrey; Stub, Dion
Abstract: Objectives: To examine predictors and outcomes of unsuccessful percutaneous coronary intervention (PCI) cases in a contemporary Australian registry cohort. Background: With improvements in techniques and pharmacotherapy in PCI, more complex lesions in older patients are now being attempted. In the context of PCI performance assessment, there are limited data regarding the characteristics and outcomes of unsuccessful PCI. Method: We prospectively collected data on patients undergoing single‐lesion PCI between 2013 and 2017 who were enrolled in the multi‐center Victorian Cardiac Outcomes Registry. Procedures were divided into two groups by whether or not PCI was deemed successful at the end of the procedure using a pre‐specified definition. Results: There were 34, 383 single‐lesion PCI performed, of which 18, 644 (54.2%) were for acute coronary syndromes. Of the study cohort, 2080 patients (6.0%) had an unsuccessful PCI – these patients were older, more likely to have previous stroke, PCI, severe left ventricular dysfunction and chronic kidney disease (all p <  0.001). The procedure was also more likely to be performed for stable angina ( p <  0.001). Chronic total occlusion PCI made up 31% of unsuccessful PCI cases. Unsuccessful PCI was itself associated with higher in‐hospital and 30‐day mortality and MACE (all p <  0.001). 4.9% of unsuccessful PCIs led to unplanned in‐hospital bypass surgery (compared to 0.2% in successful PCIs, p <  0.001). Conclusion: Our study highlights that even in contemporary PCI practice, more than 1 in 20 PCI attempts are unsuccessful. Lack of procedural success has a strong influence on patient outcomes. Monitoring rates of unsuccessful cases is an important quality assurance tool.